Verifying and Study of the Manuscripts "The Guidance of the Evaluator in Discovering the Ambiguities of the Law of Distribution of Estate" for the Scholar Mohammed the Grandson of Al-Maridini - Mohammed Sameh Mahmod Mohammed Afaneh (My University, 2005)
It's surely that it's our duty to show the efforts of our venerable scholars and our reverent ancestors who vowed and devoted themselves and their times to serve the religion of (Allah) the Great and Almighty by refuting and disapproving the excess and the extravagance of the extremists who pass themselves as invalidators and liars. It’s their right and it's our duty to preserve and save their knowledge and not to let the epochs and the years cover up and conceal their knowledge. To achieve this aim and objective, I followed the means of studying and verifying the manuscripts. God (the Great and Almighty) has granted me success to contribute and achieve this objective even with a modest but honorific effort, so my thesis involved the verification of a part from the manuscript of "Irshad Al-Farid ela Kashef Al-Gwamed men Elm Al-Fara'ad "The Guidance of the evaluator in Discovering the Ambiguities of the Law of Distribution of Estate " for the scholar Mohammed the grandson of Al- Maridini (May God be pleased with him) who died in 912 a.h. His manuscript talked about an important science of Sharia (Islamic Law), it's the of Distribution of Estate in Islam. The part that I verified contained many subjects in this law, since I started from the chapter of "Al-Munasakhat" Countermanding which deals with correcting some issues concerning the inheritance with regard to more than on dead person, then the chapter of inheritance by evaluation and precaution which contains issues of pregnancy, the poor and the epicene or androgyny persons and how to respond and reply to questions in addition what can be replied or cannot and at last how to bequeath or devise the relatives on the maternal side. I took into consideration in what mentioned above, the mentioning of the viewpoints of the legal jurists and their schools in addition to their evidences and proofs and giving preponderance or making one viewpoint outweigh another if possible. I presented for all the aforementioned the identification of the author from various sides and I offered identification to the manuscript which proves it's connection and attribution to the author. At last this is my modest effort, so if I was right and correct, it's from Allah and if I erred or was mistaken it's from my own soul and from the Satan (Devil). And the close of our supplication (cry) will be: "Praise be to Allah the Cherisher and Sustainer of the Worlds!"

إن من حق علمائنا الأجلاء وسلفنا الأبرار الذين نذروا أنفسهم وأوقاتهم لخدمة دين الله عز وجل، ينفون عنه غلو الغالين وانتحال المبطلين، من حقهم علينا أن نبرز جهدهم، ونحفظ علمهم من أن تغيبه السنون، وتطويه الأزمان، فكان تحقيق المخطوطات ودراستها وسيلة من الوسائل لتحقيق هذه الغاية، وقد وفقني الله عز وجل، لأن أشارك ولو بجهد قليل في ذلك لكنه مش رف، فكانت رسالتي هذه في تحقيق جزء من مخطوطة "إرشاد الفارض إلى كشف الغوامض من علم الفرائض" للعلامة محمد سبط المارديني رحمه الله والمتوفى سنة 912 ه. وهي مخطوطة تحدثت عن علم مهم من علوم الشريعة، وهو علم المواريث، وقد كان الجزء الذي حققته محتويًا على عدة مواضيع في هذا العلم، حيث ابتدأت العمل من باب المناسخات، والذي يهتم بتصحيح مسائل الميراث بالنظر إلى أكثر من ميت، ثم باب الميراث بالتقدير والاحتياط الذي يشمل مسائل الحمل والمفقود والخنثى، ومن ثم عن كيفية الرد ، ومن يرد عليه ومن لا يرد عليه، وأخيرًا في كيفية تورث ذوي الأرحام، وقد راعيت في جميع ما ذكر إيراد آراء الفقهاء والمذاهب وأدلتهم والترجيح بينها إن أمكن. وقد قدمت لكل ذلك بتعريف بالمؤلف استوفيت فيه جوانب كثيرة، كما وقمت بالتعريف بالمخطوطة تعريفا يثبت نسبتها لمؤلفها. وبعد فهذا جهد المقل، فإن أصبت فمن الله، وإن أخطأت فمن نفسي ومن الشيطان.
تحقيق ودراسة مخطوطة إرشاد الفارض إلى كشف الغوامض من علم الفرائض للعلامة: محمد بن سبط المارديني رحمه الله